Phytochemistry, antioxidant and anti-diabetic activities of Sterculia villosa in-vitro - Debarupa Hajra; Anirban Chouni; Santanu Paul (Elsevier, 2024)
Objective: As ongoing research continues, many anti-diabetic agents still have a multitude of side effects which is the reason why more and more people resort to traditional medicines such as Traditional Chinese Medicine (TCM). There are many Therapeutic Species of Sterculia spp. that are commonly used in TCM practices. Here, we have studied one of such TCM herbal plants, namely Sterculia villosa Roxb. (Chinese: 绒毛苹婆), for its anti-diabetic potential. In this way, the study intends to assess its effectiveness and examine its suitability as a raw natural medicine for diabetes management in traditional medicine. Method: In-vitro anti-diabetic property was evaluated by α-amylase and α-glucosidase enzyme inhibition and glucose uptake assays. Metabolomic profiling by GC-MS was conducted to determine the probable phyto-constituents in S. villosa. These phyto-compounds were further subjected to in-silico molecular docking studies, identifying stigmasterol as the most potent anti-diabetic phyto-compound. Glucose uptake efficacy was estimated by a fluorescence microplate reader employing glucose analog, 2-NBDG. Molecular dynamic studies (MDS) were carried out with GROMACS to comprehend the protein-ligand binding stability. Results: Stigmasterol showed enhanced enzyme inhibition for both α-amylase (IC50 23.84±1.37 μM) and α-glucosidase (IC50 39.56±1.5 μM). Line-weaver Burk plot revealed competitive and mixed modes of inhibition for α-amylase and α-glucosidase, respectively. The GC--MS analysis identified 23 vital phyto-compounds present in the methanolic extract of the S. villosa leaves. Upon screening against crucial anti-diabetic proteins by in-silico molecular docking, stigmasterol followed by lupeol, Stigmasta-3,5-diene, and γ-sitosterol were found to be the most effective lead compounds. Stigmasterol also showed potent hypoglycaemic efficacy, as evidenced by augmentation of 2-NBDG glucose uptake in 3T3-L1 cells. The docking and simulation studies against four crucial anti-diabetic targets, α-amylase, α-glucosidase, GLUT 4, and IRS-1, predicted that stigmasterol exhibits a multi-pronged anti-diabetic activity mediated by α-amylase inhibition and activation of IRS1 pathway, simultaneously. The MDS studies highlighted that stigmasterol showed stable interactions with these four proteins, as evidenced by the RMSD, RMSF and hydrogen bond analysis. Conclusion: The results of this study are intriguing, as they identify stigmasterol, sourced from the medicinal plant S. villosa, as a potential breakthrough in the field of diabetic remediation. This discovery paves the way for further research and development of stigmasterol as a more effective and safer treatment for diabetes.